US tightrope walk : Arab autocrats try to redefine terrorism - James M. Dorsey (2014)
The United States is walking a tightrope with US Secretary of State John Kerry’s controversial endorsement of the toppling of Egyptian President Mohammed Morsi as a “restoration of democracy”. The endorsement is likely to be seen by Islamist and non-Islamist anti-government protesters as backing for conservative Arab autocrats who project their crackdowns on opposition forces as a ‘struggle against terrorism’.That perception will gain currency as Egyptian security forces prepare to crack down on mass pro-Morsi demonstrations in Cairo.